Letter from James Curtis Booth to the Secretary of the Treasury, April 17, 1855 - Booth, James Curtis (1855)
James Curtis Booth (1810-1888) is ready to supply on demand any of the fusible alloys from 60 to 160 lbs. pressure.
Keywords: Booth, James Curtis, 1810-1888; United States. Department of the Treasury. Office of the Secretary; Alloys; United States Mint; Mint of the United States